Relative Invertebrate Abundance and Biomass in Conservation Reserve Program Plantings in Northern Missouri - Loren W. Burger Jr.; Eric W. Kurzejeski; Thomas V. Dailey; Mark R. Ryan (National Quail Symposium Proceedings, 2017)
We measured relative invertebrate abundance, biomass, and diversity in Conservation Reserve Program (CRP) fields planted to red clover (Trifolium pratense)/timothy (Phleum pratense), timothy, orchard-grass (Dactylis glomerata), tall fescue (Festuca pratensis), warm-season grasses (big bluestem [Andropogon gerardi]/switch grass [Panicum virgatum]), orchard-grass/Korean lespedeza (Kummerowia stipu/,acea), and conventionally-tilled soybeans, to assess brood habitat quality for northern bobwhite (Colinus virginkinus). We sampled invertebrate populations by vacuuming along 3 15-m transects (4.56 m2/sample) within 4 fields of each planting type, at 2-week intervals from 1 July to 15 August 1990 and 1991. Invertebrate abundance and biomass were lowest in early August (P < 0.05). The CRP fields planted to a red clover/timothy mixture, and dominated by red clover, had the highest levels of invertebrate abundance and biomass (P < 0.05). Conventionally-tilled soybeans had lower invertebrate abundance and biomass than all CRP covertypes (P< 0.05). Mean invertebrate abundance and biomass in CRP fields were 4 times that of soybean fields. In northern Missouri, CRP fields could provide quality brood habitat if structural characteristics are also consistent with brood foraging needs. Incorporation of a legume in CRP plantings may produce higher invertebrate densities and improve the value of these fields as brood habitat.
Keywords: brood ecology; brood habitat; Colinus virginianus; Conservation Reserve Program; insect; invertebrate; northern bobwhite